Structural examination to the adverbs in Omer Seyfettin’s stories - S., Baloğlu (Journal of Oriental Studies, 2020)
Our Turkish language, which offers all the possibilities of its circumstances limitless, opens different perspective to us as it reaches its profoundness. Any research on language, progress, and every conclusion reached in different subjects did not allow the final point in linguistics as in other sciences. It has also been the basis of useful linguistic works that have been continuing and continuing until now. In our article, as Omer Seyfettin’s word types in the sentences chosen from the stories are evaluated separately, the adverbs which are widely used in Turkish language are examined structurally. When this and such works are done and will be done, the writers and poets who have produced outstanding works in the field of summer will be exposed to their skillful use of language and rich vocabulary. Our aim is to show the skill of Turkish writer Omer Seyfettin in using the language and to announce to the Turkish world countries and the world. Key words: Turkish language, story, Omer Seyfettin, linguistics, adverb.